2015
DOI: 10.1186/s12891-015-0682-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression and pathological effects of periostin in human osteoarthritis cartilage

Abstract: BackgroundOsteoarthritis (OA) is one of the most common joint diseases in elderly people, however, the underlying mechanism of OA pathogenesis is not completely clear. Periostin, the extracellular protein, has been shown by cDNA array analysis to be highly expressed in OA, but its function is not fully understood. The purpose of this study was to examine the expression and function of periostin in human OA.MethodsHuman cartilage and synovia samples were used for the analysis of periostin expression and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 51 publications
10
76
0
Order By: Relevance
“…In addition, in some types of cells, periostin reportedly induces the expression of MMP family members (13,14). This induction and expression of matrix-degrading enzymes may function in tissues containing periostin, which is formed temporarily at the sites of damage to promote remodeling of the original tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in some types of cells, periostin reportedly induces the expression of MMP family members (13,14). This induction and expression of matrix-degrading enzymes may function in tissues containing periostin, which is formed temporarily at the sites of damage to promote remodeling of the original tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Periostin is considered to be an important structural mediator by balancing appropriate versus inappropriate tissue adaptation in response to insult/injury. Certain studies have shown that periostin is up-regulated in OA tissues (12)(13)(14). Previously, we reported that the periostin levels in synovial fluid were upregulated during the progression of OA in vivo, while in vitro experiments using human fibroblast-like synoviocytes suggested that addition of periostin mediated increased matrix metalloproteinase (MMP)-9 production (15).…”
mentioning
confidence: 99%
“…Expression of periostin was previously shown to be elevated in OA cartilage compared to normal, and located in the pericellular ECM close to damaged areas of cartilage [46,47]. Periostin is able to increase expression of IL-6, IL-8, MMP-1,-3,-13 and a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS)-4 by chondrocytes in vitro [46,47].…”
mentioning
confidence: 99%
“…Moreover, periostin induces inflammatory cytokines and MMPs via nuclear factor κB signaling, and promotes cartilage degeneration in patients with OA (30,31). Previous studies have demonstrated that the Postn expression is upregulated in the damaged cartilage of patients with knee OA (32)(33)(34). These observations suggest that GlcNAc has the potential to inhibit the degradation of type II collagen, as evidenced by the suppression of the level of C2C, a type II collagen degradation marker, by downregulating the expression of periostin.…”
Section: Discussionmentioning
confidence: 93%